A Comparative Study Of Anemia In Normal Patients And Patients With Renal Failure (Journal of Pharmaceutical Negative Results, 2023)
Anemia is a frequent consequence of chronic kidney disease (CKD), and it raises morbidity and death rates while also lowering quality of life. This research was conducted from March 2021 to July 2021 at the labs of General Benjawad Hospital with the goal of exploring the associations between the hematological parameters Hb, RBC, HCT, and MCV in patients with chronic renal failure and various physiological and biochemical characteristics. Thirteen patients with renal failure and 33 healthy individuals' blood samples were collected (Male n=19; Female n= 27). According to the current study, 63% of healthy individuals had severe anemia. Mean corpuscular low was seen in 87% of normal individuals (n=29) and 69% of renal failure patients (n=9), respectively. Further, thirteen healthy people and three patients with renal failure had low ferritin levels. RBC production, function, and other physical attributes were impacted by renal failure. The goal of treating anemia caused by chronic renal illness is to boost red blood cell production and renal function. As a result, erythropoiesis-stimulating agents (ESAs) and iron supplements are the preferred treatments for anemia of CKD.